Higher Education Reform in Moldova: Achievements and Challenges - Wetzinger, Johannes (International Higher Education, 2019)
The higher education system in the Republic of Moldova has undergone a far-reaching transformation since the collapse of the Soviet Union in 1991. This article analyses some of the main achievements and challenges of the higher education reform in that Eastern European country, which joined the Bologna process in 2005.